Protein structure characterization with mass spectrometry. Issue 1 (2004) - Kriwacki Kriwacki, Richard Richard; Reisdorph Reisdorph, Nichole Nichole; Siuzdak Siuzdak, Gary Gary
Abstract : Mass spectrometry is now commonly being used to determine both the primary and higher order structures of proteins. The basis for these investigations lies in the ability of mass analysis techniques to detect changes in protein conformation under differing conditions. These experiments can be conducted on proteins alone (with no modifying substance present) or in combination with proteolytic digestion or chemical modification. In addition to primary structure determination, proteases and chemical modification have long been used as probes of higher order structure, an approach that has been recently rejuvenated with the emergence of highly sensitive and accurate mass analysis techniques. Here, we review the application of proteases as probes of native structure and illustrate key concepts in the combined use of proteolysis, chemical modification, and mass spectrometry. For example, protein mass maps have been used to probe the structure of a protein/protein complex in solution (cell cycle regulatory proteins, p21 and Cdk2). This approach was also used to study the protein/protein complexes that comprise viral capsids, including those of the common cold virus where, in addition to structural information, protein mass mapping revealed mobile features of the viral proteins. Protein mass mapping clearly has broad utility in protein identification and profiling, yet its accuracy and sensitivity is also allowing for further exploration of protein structure and even structural dynamics.